1998
DOI: 10.1097/00004647-199801000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Interictal Seizure Resections Show Two Configurations of Endothelial Glut1 Glucose Transporter in the Human Blood–Brain Barrier

Abstract: Immunogold electron microscopy was used to analyze and quantify the Glut1 glucose transporter in brain tissue from five patients undergoing surgery for treatment of seizures. Samples were prepared from two different regions of each resection: (1) the most actively spiking epileptogenic site, and (2) the least actively spiking region, as indicated by intraoperative EEG monitoring. Two configurations of endothelial cell Glut1 were observed. About one half of the capillary profiles examined displayed abundant Glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
67
0
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 93 publications
(75 citation statements)
references
References 31 publications
7
67
0
1
Order By: Relevance
“…In turn, cerebral blood flow rises and large cerebral arteries dilate, which leads to increased blood pressure in brain capillaries, small arteries and veins (Ndode-Ekane et al, 2010), and triggers barrier leakage. Consistent with this, extravasation of blood albumin into the brain was found specifically in regions with more EEG spiking activity in humans (Cornford et al, 1998). However, the duration of increased blood pressure is critical and determines the severity of barrier leakage.…”
Section: Blood Pressuresupporting
confidence: 61%
See 1 more Smart Citation
“…In turn, cerebral blood flow rises and large cerebral arteries dilate, which leads to increased blood pressure in brain capillaries, small arteries and veins (Ndode-Ekane et al, 2010), and triggers barrier leakage. Consistent with this, extravasation of blood albumin into the brain was found specifically in regions with more EEG spiking activity in humans (Cornford et al, 1998). However, the duration of increased blood pressure is critical and determines the severity of barrier leakage.…”
Section: Blood Pressuresupporting
confidence: 61%
“…As a consequence, impaired bloodbrain barrier integrity causes transient barrier leakage, which allows entry of blood borne molecules into the brain (Ndode-Ekane et al, 2010;Seiffert et al, 2004;Sokrab et al, 1989;Van Vliet et al, 2007). It has been shown that seizure duration correlates with reduced barrier function (Cornford & Oldendorf, 1986), and it has been demonstrated that increased blood-brain barrier permeability in epilepsy is limited to anatomically specific brain regions (Bradbury, 1979;Cornford et al, 1998;Nitsch & Klatzo, 1983;Oztas & Sandalci, 1984). Interestingly, brain regions with increased barrier permeability are often anatomically congruent with the brain regions that are implicated in the development and propagation of seizures.…”
Section: Blood-brain Barrier Leakage In Epilepsymentioning
confidence: 99%
“…2), the contiguous larger type A endothelial cells showed a 5-to 10-fold greater expression of membrane GLUT1 transporter protein. 2 The fact that red cells seen in the lumens of both type A and B capillaries exhibited identical concentrations of membrane GLUT1 emphasized that the phenomenon was not an artifact of fixation or immunogold staining (FIG. 2).…”
Section: High-(type A) and Low-glut1-expressing (Type B) Capillariesmentioning
confidence: 98%
“…The distance separating the luminal and abluminal capillary membranes is 300 -500 nm in human brain microvessels. 2 The association of abluminal capillary cell membrane with the surrounding glial end-foot processes is equally intimate in normal brain, but it can be reduced 3 or significantly thickened 4 in pathological conditions. The basal lamina is an acellular membrane composed of type IV collagen, fibronectin, and laminin interposed between endothelial cells and astrocytic end feet.…”
Section: Introductionmentioning
confidence: 99%
“…that GLUT-1 immunoreactive epitopes in the mammalian CNS are only found at the brain capillary or pericyte. Other electron microscopy studies on human brain have shown with colabeled GLUT-1 and glial fibrillary acidic protein, distinct and separate expression of (10-nm gold) GLUT-1 in the endothelia, and (20-nm gold) GFAP in glial cells (Cornford et al, 1998b;Cornford and Hyman, 2005).…”
Section: Discussionmentioning
confidence: 89%